Suicide: A Solution to the Problem of the Absurd? - Zacharakis, Miron (Conatus - Journal of Philosophy, 2017)
Book Review of Albert Camus, Le mythe de Sisyphe: Essai sur l’absurde (Paris: Gallimard, 1989).